2020
DOI: 10.3847/2041-8213/ab6e70
|View full text |Cite
|
Sign up to set email alerts
|

On the Possibility of GW190425 Being a Black Hole–Neutron Star Binary Merger

Abstract: We argue that the kilonova/macronova associated with the gravitational-wave event GW190425 could have been bright enough to be detected if it was caused by the merger of a low-mass black hole and a neutron star. Although tidal disruption occurs for such a low-mass black hole as is generally expected, the masses of the dynamical ejecta are limited to 10 −3 M , which is consistent with previous work in the literature. The remnant disk could be as massive as 0.05-0.1M , and the disk outflow of ∼ 0.01-0.03M is lik… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

3
55
1

Year Published

2020
2020
2021
2021

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 80 publications
(59 citation statements)
references
References 75 publications
3
55
1
Order By: Relevance
“…The presence of NSs in a binary can leave behind relativistic ejecta that predominantly contain energetic neutrons, which source r-process heavy elements and kilonovae [19]. Indeed several studies used electromagnetic information to understand whether the low-mass compact binary mergers detected so far are BHNS or BNS systems [20][21][22][23][24]. However, if the primary companion is a massive BH (where the precise mass threshold depends on the BH spin [25][26][27]) then no ejecta might be left behind, as tidal forces will be small.…”
Section: Introductionmentioning
confidence: 99%
“…The presence of NSs in a binary can leave behind relativistic ejecta that predominantly contain energetic neutrons, which source r-process heavy elements and kilonovae [19]. Indeed several studies used electromagnetic information to understand whether the low-mass compact binary mergers detected so far are BHNS or BNS systems [20][21][22][23][24]. However, if the primary companion is a massive BH (where the precise mass threshold depends on the BH spin [25][26][27]) then no ejecta might be left behind, as tidal forces will be small.…”
Section: Introductionmentioning
confidence: 99%
“…Owing to the wideness of the Regge gaps, the range of detectable spin-2 masses is larger than in the scalar case and similar to the vector case. If (spinning) BHs of a few solar masses are detected [93], they can probe m b ∼ 10 −10 eV, whereas BHs as massive as M87 can reach the other hand of the spectrum, m b ∼ 10 −21 eV, where ultralight bosons are also compelling dark-matter candidates [16].…”
mentioning
confidence: 99%
“…As of this writing, in O3, the LIGO and Virgo Collaborations have published seven circulars via the Gamma-ray Coordinates Network (GCN) describing detection candidates for which the probability of the system being a NSBH is larger than 1% and for which the candidate has not been retracted [10][11][12][13][14][15][16]. Furthermore, GW data alone do not exclude the possibility that GW170817 is a NSBH [17][18][19], and it has also been suggested that GW190425 could be a NSBH [20,21]. Therefore it is timely to develop methods that can be used to study NSBHs in GW data.…”
mentioning
confidence: 99%